Developing a Values Teaching Education Program for Preservice Teachers and Evaluating its Effectiveness - PALA, Aynur; Yildiz, Derya Göğebakan (Asian Journal of Education and Training, 2021)
The aim of this project was to develop an 8-week values education program and evaluate how well it raises preservice teachers’ awareness of values education. This was an experimental and qualitative study conducted in April - May 2019 in eight 70-minute lectures at the Faculty of Education of Manisa Celal Bayar University. An 8-week values education program was developed, then, its effectiveness was evaluated using an experimental pretest-posttest control group design. The sample consisted of 47 students (35 females, 12 males) randomly assigned to two groups: Data were collected using a demographic characteristics form and the Schwartz Value Survey, which consists of 56 values. The values education program was based on eight values derived from the Schwartz Value Survey. A qualitative research method was also used. Data were collected through semi-structured interviews conducted by the researchers. Research results showed that The Values Teaching Educational Program-developed by researchers- had a positive effect on values such as responsibility, social justice, modesty, open-mindedness, protecting environment, honesty, and helpfulness. But it was not found statistically significant difference between control group and experimental group over “successful” value. The qualitative results also show that the values education program met participants’ expectations and improved their perceptions and awareness of values and their motivation to put them in practice. Lastly, the values education program helped the experimental participants develop positive views of the program itself and its content, material, activities, duration and the group leader.